The Advantage of Bevacizumab in Treating Colorectal Brain Metastasis - 陳鴻明(Hung-Ming Chen); 鄧豪偉(Hao-Wei Teng) (Journal of Cancer Research and Practice, 2014)
Abstract Bevacizumab is known to be a humanized monoclonal antibody that inhibits vascular endothelial growth factor. It is used to treat varied kinds of cancers, such as breast cancer, colorectal cancer, non-small cell lung cancer, high grade glioma and etc. While it do appear to delay cancer progression, it is not a curative approach. Because of its high molecular weight, bevacizumab would be believed to be not cross the blood- brain barrier. However, this theory is to be challenged by series of studies proving the efficacy of bevacizumab in brain tumor. On account of lack of vital information about safety events and increasing risk of intra-cranial hemorrhage, Food and Drug Administration (FDA) lifted the ban on use of bevacizumab in colorectal cancer with brain metastasis since several years ago. Therefore, the reports of use of bevacizumab in colorectal cancer with brain metastasis are limited. Here, we presented a case of colorectal cancer with brain metastasis, and the brain lesion got shrinkage after starting bevacizumab in combination with chemotherapy.